Biopsychosocial Factors Associated with the Occurrence of Female Infertility - Sari, Suci Arsita; Budihastuti, Uki Retno; Pamungkasari, Eti Poncorini (Journal of Maternal and Child Health, 2019)
Background: Infertility is not a disease that needs to be worried. However, it becomes a serious problem for certain people such as causing divorce. Infertility in women can be affected by Polycystic Ovary Syndrome (PCOS), Body Mass Index (BMI), lifestyle, age, occupation, stress, metabolic disorder, endometriosis, and uterine myoma. This study aimed to determine the factors associated with female infertility.Subjects and Method: This was an analytic observational study with a case-control design. This study was conducted at Dr. Moewardi hospital, Surakarta, Central Java, from May to July 2019. A sample of 200 women was selected by fixed disease sampling. The dependent variable was infertility. The independent variables were PCOS, BMI, lifestyle, age, occupation, stress, metabolic disorder, endometriosis, and uterine myoma. The data were collected by questionnaire and medical record. The study was analyzed by multiple logistic regression.Results: Female infertility was affected by age ?35 years (OR= 9.05; 95% CI= 2.61 to 31.39; p= 0.001), occupation (OR= 8.29; 95% CI= 2.25 to 30.48; p= 0.001), BMI ?25 (OR= 8.16; 95% CI= 2.44 to 27.29; p=0.001), PCOS (OR=117.34; 95% CI=10.31 to 1334.83; p <0.001), endometriosis (OR= 5.01; 95% CI= 1.17 to 21.38; p=0.029), uterine myoma (OR=6.59; 95% CI= 1.76 to 24.67; p= 0.005), and metabolic disorder (OR= 15.39; 95% CI= 4.02 to 58.84; p<0.001).Conclusion: Female fertility is affected by age ?35 years, occupation, BMI ?25, PCOS, endometriosis, uterine myoma, and metabolic disorder.Keywords: female infertility, PCOS, endometriosisCorrespondence:Suci Arsita Sari. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36 A, Surakarta 57126, Central Java. Email: suciarsita@gmail.com. Mobile: 085786179994.Journal of Maternal and Child Health (2019), 4(6): 507-515https://doi.org/10.26911/thejmch.2019.04.06.11